Developing Students’ Descriptive Text Writing Abilities Using The Think Talk Write Learning Model (T/N) TO Students’ of Grade V of State Elementary School 155 Matinggi Vegetables in Penyambungan, Mandailing - Sutikno; Laila Fitriani (International Journal of Educational Research Excellence (IJERE), 2025)
The appropriate learning model for writing descriptive text is he Think Talk Write (TTW) model. How does the use of the Think Talk Write (TTW) learning model affect the ability to write descriptive text in class V of SD Negeri Number 155 Sayur Matinggi? The aim of this research is to describe the effectiveness of using the Think Talk Write (TTW) learning model on the ability of class V students at SD Negeri Number 155 Sayur Matinggi to write descriptive text. This research uses a quantitative approach with a type of pre-experimental design that is included in the experimental research. The test was performed twice, during the pretest and posttest. Based on the results of the research and discussion, it can be concluded that the ability to write descriptive paragraphs for Class V students at State Elementary School Number 155 Sayur Matinggi before using the Think Talk Write (TTW) learning model obtained an average score of 42.75 with a very poor category. Meanwhile, the ability to write descriptive paragraphs for class V students at State Elementary School Number 155 Sayur Matinggi after using the Think Talk Write (TTW) learning model obtained an average score of 78.27 in the sufficient category. The results of hypothesis testing using SPSS version 23 show that the tcount value obtained is = 11.892, while the ttable value is = 1.701 with a significance level of 0.05, so it is stated that the research hypothesis is accepted because the tcount value > ttable value (11.892 > 1,701). Therefore, it can be concluded that the application of the Think Talk Write learning model has an effect on the ability of class V students at State Elementary School Number 155 Sayur Matinggi to write descriptive paragraphs